Clinical and prognostic significance of serum transforming growth factor-beta1 levels in patients with pancreatic ductal adenocarcinoma - Zhao,J. (2016)
Pancreatic ductal adenocarcinoma (PDAC) has a poor 5-year survival rate of 5%. Biomarkers for the early detection of pancreatic cancer are urgently needed. Transforming growth factor-beta1 (TGF-β1) is elevated in the tissues and plasma of patients with PDAC. However, no studies systemically report prognostic significance of plasma TGF-β1 levels in PDAC. In the present study, we assessed the prognostic significance of serum TGF-β levels in patients with PDAC. TGF-β levels were determined in serum from 146 PDAC patients, and 58 patients with benign pancreatic conditions. Regression models were used to correlate TGF-β levels to gender, age, stage, class, and metastasis. Survival analyses were performed using multivariate Cox models. Serum levels of TGF-β1 distinguished PDAC from benign pancreatic conditions (P<0.001) and healthy control subjects (P<0.001). Serum levels of TGF-β also distinguished tumor stage (P=0.002) and lymph node metastasis (P=0.001). High serum levels of TGF-β1 were significantly correlated with reduced patient survival. Multivariate analysis revealed that TGF-β1, lymph node metastasis and tumor stage were independent factors for PDAC survival. Our results indicate that serum TGF-β1 may be used as a potential prognostic marker for PDAC.